MG132‐induced progerin clearance is mediated by autophagy activation and splicing regulation - Karim Harhouri; Claire Navarro; Danielle Depetris; Marie‐Geneviève Mattei; Xavier Nissan; Pierre Cau; Annachiara De Sandre‐Giovannoli; Nicolas Lévy (EMBO Molecular Medicine, 2017)
Abstract Hutchinson–Gilford progeria syndrome (HGPS) is a lethal premature and accelerated aging disease caused by a de novo point mutation in LMNA encoding A‐type lamins. Progerin, a truncated and toxic prelamin A issued from aberrant splicing, accumulates in HGPS cells' nuclei and is a hallmark of the disease. Small amounts of progerin are also produced during normal aging. We show that progerin is sequestered into abnormally shaped promyelocytic nuclear bodies, identified as novel biomarkers in late passage HGPS cell lines. We found that the proteasome inhibitor MG132 induces progerin degradation through macroautophagy and strongly reduces progerin production through downregulation of SRSF‐1 and SRSF‐5 accumulation, controlling prelamin A mRNA aberrant splicing. MG132 treatment improves cellular HGPS phenotypes. MG132 injection in skeletal muscle of LmnaG609G/G609G mice locally reduces SRSF‐1 expression and progerin levels. Altogether, we demonstrate progerin reduction based on MG132 dual action and shed light on a promising class of molecules toward a potential therapy for children with HGPS.